Understanding the temperature- and pressure-dependent electronic properties of FeSi: DFT + DMFT study. (28th December 2020) - Dutta, Paromita; Pandey, Sudhir K.
Abstract: Electronic structures of FeSi and Fe1.02 Si0.98 under pressure (achieved through volume compression) have been investigated by using DFT+DMFT and KKR-CPA methods, respectively. The widening of band gap with increasing pressure suggests that the experimentally observed insulator-to-metal transition temperature should shift towards the higher temperature for FeSi. KKR-CPA calculations have shown the presence of impurity states in the gapped region which predicts the half-metallic nature. The closure of the gap (in one spin channel) with pressure increment appears to be responsible for the experimentally observed semiconductor-to-metal transition in Fe excess samples at a temperature below 50 K. Magnetic moments at Fe excess sites are found to be decreasing with increasing pressure from per Fe atom ( ) to per Fe atom ( ). Moreover, for FeSi the calculated local spin susceptibility has shown decreasing behavior with pressure rise similar to experimental result.